Rewriting the transcriptome: adenosine-to-inosine RNA editing by ADARs - Carl R. Walkley; Jin Billy Li (Genome Biology, 2017)
Abstract One of the most prevalent forms of post-transcritpional RNA modification is the conversion of adenosine nucleosides to inosine (A-to-I), mediated by the ADAR family of enzymes. The functional requirement and regulatory landscape for the majority of A-to-I editing events are, at present, uncertain. Recent studies have identified key in vivo functions of ADAR enzymes, informing our understanding of the biological importance of A-to-I editing. Large-scale studies have revealed how editing is regulated both in cis and in trans. This review will explore these recent studies and how they broaden our understanding of the functions and regulation of ADAR-mediated RNA editing.